SPECIFICATION OF THE SIGNIFICANCE OF THE PRINCIPLE OF DETERMINISM IN MODERN SCIENTIFIC THEORY - Kubalskyi , Oleh (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2022)
Determinism appears as a key concept for science from the moment of its emergence: science is designed to clearly and unambiguously determine the causes of observed phenomena and, on this basis, confidently predict the development of these phenomena. However, more than a century ago, after the emergence of quantum physics and the formulation of the theory of relativity and the principle of uncertainty, the classical understanding of determinism underwent a significant revision in physics, which was considered a model of science. Even more challenges to the concept of determinism have been received in the social sciences and humanities, which address objects that cannot be fully grasped by human experience and tested through experiments. At the same time, it is the social sciences and humanities that are increasingly being turned to for answers to the questions of what the future of society will look like and how to prepare for its challenges. All this led to the need to clarify to what extent the concept of determinism itself has retained its significance for science, as well as to clarify the modern understanding of concepts related to it, such as causality, indeterminism, uncertainty, etc. Important ideas and problems that have not been adequately understood to date were formulated in the classic works of prominent representatives of the natural sciences and humanities, in particular, such as the physicist Werner Heisenberg and the historian and sociologist Raymond Aron. With the development of science, the concept of causality only becomes more complicated and develops as a theoretical justification of the relations of causality, determinism and interdependence, and at the same time as an approximate model of causality as an objective and regular relationship of things, processes and phenomena. A separate task of science is to carry out a public clarification of essential changes in the concept of scientific determinism as an assumption about possible stable repeated connections, without which, however, scientific or even quasi-scientific systematization of knowledge is impossible.